Evaluation depth of the curve of Spee in class I, class II, and class III malocclusion: A cross sectional study - Sanjna Nayar; V Dinakarsamy; S Santhosh (Wolters Kluwer Medknow Publications, 2015)
Occlusal plane is an essential consideration when multiple long-span posterior restorations are designed. When restorations are added to an existing tooth arrangement characterized by rotated, tipped, or extruded teeth, excursive interferences may be incorporated, resulting in detrimental squeal. The curve of Spee, which exists in the ideal natural dentition, allows harmony to exist between the anterior tooth and condylar guidance. This curve exists in the sagittal plane and is the best viewed from a lateral aspect. It permits total posterior disclusion on mandibular protrusion, given proper anterior tooth guidance. It is unclear that whether the curve of Spee is a description of the occlusal surface of each arch separately or in maximal intercuspation. The purpose of this study was to examine the differences in the depth of curve of Spee between the class I, class II, class III and to investigate the relationship of depth of curve of Spee with over jet, over-bite.